Hafez’s and Molavi’s Ideas on Meaning - Saghe’i, Saeed (Richtmann Publishing, 2011)
Molavi (=Rumi) and Hafez, two Iranian poets in two succeeding centuries, have each their own ideas on meaning. Molaviuses tales with human or animal characters in a symbolic and multi-layered fashion and Hafez makes use of the natural element of SabaWind as a channel for transferring a pleasant scent between the lover and beloved, and, thus, in this way they both confirm theories ofmeaning in the communication process. Case studies of Hafez’s and Molavi’s poetry showed that they, not unlike contemporary westernthinkers such as David Berlo and Dean Barnlund, believe that communication is the process of transfer of the message from sender toreceiver providing the meaning received by the receiver be similar to that intended by the sender. This aim became possible throughcomparing Berlo’s famous communication model with Hafez’s and Molavi’s poems. The results will be presented in tables and diagramsand, finally, an answer will be attempted to the question as to whether it is possible to find a connection between prevailing westerntheories in this field and the points mentioned by Hafez and Molavi.